Long-Term Blood Pressure Control After Hypertensive Pregnancy Following Physician-Optimized Self-Management: The POP-HT Randomized Clinical Trial - Kitt, Jamie; Fox, Rachael; Frost, Annabelle; Shanyinde, Milensu; Tucker, Katherine; Bateman, Paul A; Suriano, Katie; Kenworthy, Yvonne; McCourt, Annabelle; Woodward, William; Lapidaire, Winok; Lacharie, Miriam; et al. (JAMA : the journal of the American Medical Association, 2023)
IMPORTANCE: Pregnancy hypertension results in adverse cardiac remodeling and higher incidence of hypertension and cardiovascular diseases in later life. OBJECTIVE: To evaluate whether an intervention designed to achieve better blood pressure control in the postnatal period is associated with lower blood pressure than usual outpatient care during the first 9 months postpartum. DESIGN, SETTING, AND PARTICIPANTS: Randomized, open-label, blinded, end point trial set in a single hospital in the UK. Eligible participants were aged 18 years or older, following pregnancy complicated by preeclampsia or gestational hypertension, requiring antihypertensive medication postnatally when discharged. The first enrollment occurred on February 21, 2020, and the last follow-up, November 2, 2021. The follow-up period was approximately 9 months. INTERVENTIONS: Participants were randomly assigned 1:1 to self-monitoring along with physician-optimized antihypertensive titration or usual postnatal care. MAIN OUTCOMES AND MEASURES: The primary outcome was 24-hour mean diastolic blood pressure at 9 months postpartum, adjusted for baseline postnatal blood pressure. RESULTS: Two hundred twenty participants were randomly assigned to either the intervention group (n = 112) or the control group (n = 108). The mean (SD) age of participants was 32.6 (5.0) years, 40% had gestational hypertension, and 60% had preeclampsia. Two hundred participants (91%) were included in the primary analysis. The 24-hour mean (SD) diastolic blood pressure, measured at 249 (16) days postpartum, was 5.8 mm Hg lower in the intervention group (71.2 [5.6] mm Hg) than in the control group (76.6 [5.7] mm Hg). The between-group difference was −5.80 mm Hg (95% CI, −7.40 to −4.20; P < .001). Similarly, the 24-hour mean (SD) systolic blood pressure was 6.5 mm Hg lower in the intervention group (114.0 [7.7] mm Hg) than in the control group (120.3 [9.1] mm Hg). The between-group difference was −6.51 mm Hg (95% CI, −8.80 to −4.22; P < .001). CONCLUSIONS AND RELEVANCE: In this single-center trial, self-monitoring and physician-guided titration of antihypertensive medications was associated with lower blood pressure during the first 9 months postpartum than usual postnatal outpatient care in the UK. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT04273854